Infection with blast fungus (Magnaporthe orzyae) leads to increased expression of an arabinogalactan-protein epitope in both susceptible and resistant rice cultivars. (April 2018) - Liang, Yanli; Zhao, Jing; Wang, Congde; Jing, Yang; Chengyun, Li; Baldwin, Timothy C.
Abstract: Blast fungus ( Magnaporthe orzyae) is the most serious pathogen of rice. As such, the objective of the current study was to investigate the infection process using a selected panel of anti-plant extracellular matrix antibodies, in infected leaves from three rice cultivars that display varying degrees of resistance to the pathogen; at selected time points post inoculation. An arabinogalactan-protein (AGP) epitope, recognized by the antibody JIM13, was shown to be temporally and spatially regulated during the infection, in all three cultivars. Prior to inoculation, expression of the epitope was confined to the epidermis, sclerenchyma, phloem, xylem and bundle sheath. As the infection progressed, the intensity of labeling increased in all the aforementioned cell types and spread to the mesophyll. Immunogold transmission electron microscopy, revealed this epitope to be most abundant at the plasma membrane. These data suggest that this epitope is borne on a plasma-membrane-associated AGP, which may act as a pattern recognition receptor (PRR), involved in the basal immune response to infection with blast fungus, in both resistant and susceptible rice cultivars. As such, this study represents the first report of a membrane – associated arabinogalactan-protein in rice, which once cloned, could be of utility in future breeding programs/genetic modification to improve the basal immune response to blast fungus and other pathogens, in this globally important food crop. Highlights: Rice arabinogalactan protein (AGP) epitope detected. Rice AGP epitope upregulated upon infection with blast fungus. AGP may act as pattern recognition receptor in basal immune response. Possible application in future breeding programmes.